What can repetition, reading and naming tell us about Jargon aphasia?. (February 2019) - Pilkington, Emma; Sage, Karen; Saddy, James Douglas; Robson, Holly
Abstract: Jargon aphasia is an acquired language disorder characterised by high proportions of nonword error production, rendering spoken language incomprehensible. There exist two major hypotheses relating to the source of nonword error; one implicates disruption to phonological processing and the other suggests both phonological and lexical contributions. The lexical sources are described as failure in lexical retrieval followed by surrogate phonological construction, or a lexical selection error further compounded by phonological breakdown. The current study analysed nonword error patterns of ten individuals with fluent neologistic Jargon aphasia in word repetition, reading and picture naming to gain insights into the contributions of these different sources. It was predicted that, if lexical retrieval deficits contribute to nonword production, naming would produce a greater proportion and severity of nonword errors in comparison to repetition and reading, where phonology is present and additional nonlexical processing can support production. Both group and case series analyses were implemented to determine whether quantity and quality of nonwords differed across the three production tasks. Nonword phoneme inventories were compared against the normative phoneme distribution to explore whether phonological production takes place within a typically organised, lexically constrained system. Results demonstrated fewer nonword errors in naming and a tendency for nonwords in naming to be characterised by lower phonological accuracy. However, nonwords were, for the most part, constructed with reference to target phonological information and, generally, nonword phonological production patterns adhered to the statistical properties of the learned phonological system. While a subset of the current group demonstrated very limited lexical processing capacity which manifested as nonword errors in naming being most disrupted, overall the results suggest that nonwords are largely underpinned by some degree of successful lexical retrieval and implicate phonological sources, which manifest more severely when production is accomplished via nonlexical processing routes. Highlights: Picture naming elicited fewer nonwords than reading or repetition. Nonwords in picture naming tended to have lower phonological accuracy than those from reading or repetition. Nonwords were constructed with reference to target lexico-phonological information, suggesting a phonological source. Tasks which increased focus on lexico-semantic processing reduced the likelihood of nonword production. Greater focus on phonological information increased the likelihood of observing a nonword.